Determination of Constitutive Parameters of Crystalline Limestone Based on Improved RHT Model - Hao-Fan Tian; Tai Bao; Zhuo Li; Hao Peng; Shuai You; Shi-li Xiao (Advances in Materials Science and Engineering)
This study improves the RHT constitutive model based on some shortcomings, and the main improvements work are as follows: (1) hyperbolic function is used to make up for the deficiency of tensile strain rate enhancement factor of RHT constitutive model at high strain rate; (2) considering the constant change of hydrostatic pressure, the initial damage value of rock is introduced into the constitutive model, and the improved damage accumulation expression is derived based on this value. (3) In the equation of residual failure surface, the influence of the Lode angle factor is considered, the RHT constitutive parameters of crystalline limestone are determined by the SHPB experiment, and the difference in rock failure forms before and after the correction of constitutive parameters is simulated by ANSYS/LS-DYNA software. The results show that the improved constitutive parameters can effectively represent the yield strength surface and residual strength surface of the rock, which verifies the rationality of the improved RHT constitutive model, and also shows that it is an effective and simple method to obtain RHT constitutive parameters by SHPB experiment.